The Cerro Guacha Caldera complex, SW Bolivia: a long-lived, multicyclic, resurgent caldera complex in the Altiplano-Puna Volcanic Complex of the Central Andes - Iriarte Ibañez, Alvaro Rodrigo; de Silva, Shanaka L.; Schmitt, Axel Karl; Ch, Néstor Jiménez (Journal of volcanology and geothermal research, 2024)
Measuring ∼50 × 30 km, the Cerro Guacha Caldera Complex (CGCC) is a polycyclic, nested caldera complex within the Altiplano Puna Volcanic Complex (APVC) of the Central Andes. Previous work had established that CGCC was built in three stages. Catastrophic supereruptions of the 1300 km3 (DRE - Dense Rock Equivalent) Guacha ignimbrite at ca. 5.65 Ma and the 800 km3 (DRE) Tara ignimbrite at ca. 3.49 Ma resulted in two nested caldera collapses that define the first two stages (G1C and G2C) of the CGCC. The third stage, G3C, initiated ∼1.8 Ma with the eruption of the Puripica Chico ignimbrite and associated lavas. The only previous detailed systematic study of the CGCC was of the G2C (Grocke et al., 2017a, 2017b). In this work we provide new field, petrochemical and geochronological data on the first and third cycles that now allow us to present the first comprehensive account of the eruption history, as well as the magmatic and volcanological evolution of the CGCC as a long-lived caldera complex. Erupted compositions during the G1C and G3C cycles are dominantly high-K, calc-alkaline dacites and minor andesites and these fall within the andesite to rhyolite compositional array previously defined for the G2C. In the CGCC as a whole, dacitic compositions account for over 90% of the ∼2200 km3 of magma erupted. These data reveal a consistency of magma composition, storage and evolution throughout the >4 Ma history of the CGCC. New UPb in zircon ages reveal distinct zircon age distributions that indicate that each caldera cycle represented new magmatic cycles that accumulated 10's to 100's of thousands of years prior to eruption. We find zircon antecrysts in all eruptive stages which we interpret as assimilation of non-erupted progenitors of earlier magmatic cycles. Occassional zircon xenocrysts and cores are interpreted as assimilation of upper crustal basement lithologies, supporting previous interpretations of upper crustal open system magmatic evolution for the G2C to the entire CGCC. Both the G1C and G2C calderas are west-hinged trap-door style collapses. Of these, the 5.65 Ma G1C caldera measures ∼50 km × 30 km, whereas the 3.49 Ma G2C is 30 × 20 km and is nested within the G1C. Resurgent uplift in both the calderas reveals at least a kilometer thickness of intracaldera ignimbrite. Outflow ignimbrites from the CGCC extend 100 km N-S and 40 km E-W around CGCC and were topographically limited. Intracaldera ignimbrite volume dominates outflow volumes by a ratio of ∼5:1. Repose periods between successive stages are now calculated to be 2.1 (G1C to G2C) and 1.8 (G2C to G3C) Myr respectively. The evolution of the CGCC parallels other APVC calderas and is closely linked to the history of the APVC flare-up. The two supereruptions at 5.65 Ma (Guacha Ignimbrite) and 3.49 Ma (Tara Ignimbrite) coincide with the peak of the flare-up and its eruptive and magmatic tempo correlate with the regional tempo. The eruptive and magmatic histories connote a composite granodioritic subcaldera pluton of significant extent accumulated in the upper crust beneath the CGCC.
Online veröffentlicht: 28 December 2023
Gesehen am 25.07.2024